The size effect on intermetallic microstructure evolution of critical solder joints for flip chip assemblies. Issue 4 (7th September 2015) - Tian, Ye; Chow, Justin; Liu, Xi; Sitaraman, Suresh K.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to study the intermetallic compound (IMC) thickness, composition and morphology in 100-μm pitch and 200-μm pitch Sn–Ag–Cu (SAC305) flip-chip assemblies after bump reflow and assembly reflow. In particular, emphasis is placed on the effect of solder joint size on the interfacial IMCs between metal pads and solder matrix. Design/methodology/approach – This work uses 100-μm pitch and 200-μm pitch silicon flip chips with nickel (Ni) pads and stand-off height of approximately 45 and 90 μm, respectively, assembled on substrates with copper (Cu) pads. The IMCs evolution in solder joints was investigated during reflow by using 100- and 200-μm pitch flip-chip assemblies. Findings – After bump reflow, the joints size controls the IMC composition and dominant IMC type as well as IMC thickness and also influences the dominant IMC morphology. After assembly reflow, the cross-reaction of the pad metallurgies promotes the dominant IMC transformation and shape coarsened on the Ni pad interface for smaller joints and promotes a great number of new dominate IMC growth on the Ni pad interface in larger joints. On the Cu pad interface, many small voids formed in the IMC in larger joints, but were not observed in smaller joints, combined with the drawing of the IMC growth process. Originality/value – With continued advances in microelectronics, it is anticipated that next-generation microelectronic assemblies will require a reduction of the flip-chip solder bump pitch to 100 μm or less from the current industrial practice of 130 to150 μm. This work shows that as the packaging size reduced with the solder joint interconnection, the solder size becomes an important factor in the intermetallic composition as well as morphology and thickness after reflow.